Protected Vegetable Cultivation in Haryana: An Analysis of Marketing Efficiency and Major Constraints (Indian Journal of Extension Education, 2025)
The study presents channel-wise marketing efficiency, the major marketing and production constraints faced by protected vegetable cultivators in Haryana. Using the Yamane sampling formula, a sample of 300 farmers cultivating cucumber, tomato, and capsicum was selected and primary data was collected through a pre-tested interview schedule during 2024. Marketing efficiency across major marketing channels was estimated using Acharya Modified Method, while Garrett Ranking technique was employed to prioritise key marketing and production constraints. The results revealed that direct to consumer marketing channels consistently recorded the highest marketing efficiency and farmer’s share, whereas channels involving commission agents were the least efficient due to higher marketing costs and intermediary margins. The Garrett Ranking analysis indicated that absence of minimum support price (MSP), high price fluctuations and lack of organised markets were the most severe marketing constraints. On the production side, labour shortages, high input costs, limited lifespan of polyethylene sheet and environmental pressures significantly affected profitability. The paper highlights that the issues of marketing and production are interlinked and jointly influences income stability and decision-making of protected vegetable cultivators. Strengthening market linkages, infrastructure and technical support is therefore is essential to enhance the economic viability of protected vegetable cultivation in Haryana.